High Wisdom Intelligence- Discussing Education of High Wisdom Intelligence - Ma, Wen; Zhu, Yanqin; Li, Chunli; Zhang, Bo; Tian, Xin (Advances in Social Sciences Research Journal, 2022)
The number of talented persons who are equipped with high wisdom intelligence will immediately determine the quality of humankind’s entire life, and the future trend for humankind’s innovation and creation in fields such as thinking, cognition, society, politics, economy, military, science, arts, culture, and so on. Meanwhile, it protects the harmonious development of various fields. By illustrating the meanings of applying high wisdom intelligence in the survival and prosperity for each nation, ethnicity and individual, this article has a significant application to the understanding of educational studies of highwisdom intelligence.